AN UP-TO-DATE REVIEW: MICROSPHERES AS A NEW DRUG DELIVERY SYSTEM - DESNITA, RISE; NOVIANA, EKA; ZAI, KHADIJAH; SAIFULLAH SULAIMAN, TEUKU NANDA (International Journal of Applied Pharmaceutics, 2023)
The application of microsphere systems in drug preparations has seen a significant increase in recent years for various purposes. Microsphere systems can be utilized in a range of drug preparations, utilizing polymer types that are appropriate for the intended release target. Microspheres offer numerous benefits and can be used in various applications, including spacer applications, medication administration, and medical diagnostics. Microspheres have minimal negative effects, a more extended therapeutic effect, require fewer doses, and provide more consistent medication absorption. Additionally, they are adaptable, offer effective encapsulation, and are cost-effective. This overview was compiled to provide an up-to-date summary of the latest developments in new drug delivery systems utilizing microsphere dosage forms. Literature from Scopus, ScienceDirect, and PubMed from 2019 to 2022 was searched to provide the latest information. The use of microsphere systems is categorized into various new drug delivery routes, including gastroretentive, colon, nasal and pulmonary, parenteral, ocular, and topical applications.